Massive mortality of invasive bivalves as a potential resource subsidy for the adjacent terrestrial food web - Bódis, E. (2014)
Large-scale mortality of invasive bivalves was observed in the River Danube basin in the autumn of 2011 due to a particularly low water discharge. The aim of this study was to quantify and compare the biomass of invasive and native bivalve die-offs amongst eight different sites and to assess the potential role of invasive bivalve die-offs as a resource subsidy for the adjacent terrestrial food web. Invasive bivalve die-offs dominated half of the study sites and their highest density and biomass were recorded at the warm water effluent. The density and biomass values recorded in this study are amongst the highest values recorded for aquatic ecosystems and show that a habitat affected by heated water can sustain an extremely high biomass of invasive bivalves. These mortalities highlight invasive bivalves as a major resource subsidy, possibly contributing remarkable amounts of nutrients and energy to the adjacent terrestrial ecosystem. Given the widespread occurrence of these invasive bivalves and the predicted increase in the frequency and intensity of extreme climatic events, the ecological impacts generated by their massive mortalities should be taken into account in other geographical areas as well.